STUDENT PROBLEMS IN THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING AT SMPS ANJANGSANA KECAMATAN MUNTE KABUPATEN KARO - Aloken Marwahta Br Ginting; Mohammad Al Farabi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research aims to analyze the challenges faced by Muslim students in participating in Islamic Religious Education (PAI) at SMPS Anjangsana, Munte District, Karo Regency. This school is located in a predominantly non-Muslim area, and Muslim students being a minority facing various challenges from social, cultural, and technical learning perspectives. The research method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews with Muslim students, PAI teachers, and the school principal, as well as field observations and document studies.The research results indicate that the problems faced include the limited number of Muslim students, so PAI learning is carried out separately and with minimal interaction, very limited learning support facilities and infrastructure for PAI, social pressure and feelings of alienation in the school environment, and low student motivation and participation in learning due to a lack of psychosocial support and facilities. This research recommends strategies to strengthen inclusive education based on Islamic values and tolerance, increase support for learning facilities, and provide teacher training in managing differentiated learning in a multicultural environment. These findings contribute to the development of Islamic religious education models in Muslim minority areas.